(3OjhGf GdJgGejs - (3Ydj Hf eMeO Hf agO, CHh GdMSf GdJgGej,J (B416 (3g` s
(3ChdgG (B:s
(3bGd GdJgGejR jeOM GdCejf fUQ GdOhdI eQhGf HejGaGQbjf YHS ef TYQ aj GdQCS eQJSe eG faqQ GdHjV eKd GdHjV aj Gddee s
(3BNQgG (B:s
(3ef bUjOI jeOM HgG GdTQja CHGGdMSf YHGSkG BNQgG(B: (3dG ojaJfi GdYdjGA EdG HGdXHi bOeG EPG s
(3fSNI KGfjI GdNW eged GdfbW bdjdkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B145 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B219s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B61 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B771s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs